The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5430/cns.v4n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of smartphone use in monitoring pain and symptoms among patients with serious illness

Abstract: Background: Little is known about the feasibility and acceptability of using mobile technology among seriously ill older adults experiencing moderate to severe pain. Objective: A smartphone application was tested for feasibility and acceptability of use among ethnically-diverse older adults experiencing moderate to severe pain. Additionally, authors aimed to document patient perceived barriers and facilitators of using the mobile device for pain monitoring. Methods: Twenty-three participants were enrolled in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Although most participants reported an attempt to self-manage their pain and symptoms, lack of knowledge about how to do so was a major barrier. Similar to other populations (Valenti et al, 2016), we found that patients with mTBI did want to use an app to help them with managing their pain and symptoms. Among our participants, returning to school after injury and completing homework assignments was a major challenge.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although most participants reported an attempt to self-manage their pain and symptoms, lack of knowledge about how to do so was a major barrier. Similar to other populations (Valenti et al, 2016), we found that patients with mTBI did want to use an app to help them with managing their pain and symptoms. Among our participants, returning to school after injury and completing homework assignments was a major challenge.…”
Section: Discussionsupporting
confidence: 77%
“…For example, ranking items by importance, as seen in the PainTracker computerized questionnaire, might be beneficial for those with TBI who have multiple issues to address when they meet with their healthcare providers. Suggestions from Valenti et al (2016) study about increasing font size and working around scrolling capacity might make the application more usable for those with sensory issues, as well as older adults. The 2-way messaging capabilities explored by Jamison and et al (2017) might be able to increase use of the application in some participants.…”
Section: Current Informatics Tools To Support Pain Self-managementmentioning
confidence: 99%